Anticoagulant activity of a sulfated chitosan. - Vongchan P. (2014)
Chitin prepared from the shells of rice-field crabs (Somanniathelphusa dugasti) was converted into chitosan with a degree of acetylation of 0.21 and then sulfated with chlorosulfonic acid in N,N-dimethylformamide under semi-heterogeneous conditions to give 87% of water-soluble sulfated chitosan with degree of substitution (d.s) of 2.13. 1H NMR revealed the sulfate substitution at C-2, C-3 and C-6. Gel filtration on Sepharose CL-6B of the sulfated chitosan gave three fractions with average molecular weights of 7.1, 3.5, and 1.9 x 10(4). The three sulfated chitosan preparations showed strong anticoagulant activities, with the same mechanism of action observed for standard therapeutic heparin.